Too good to be true: How Argentinian audiences read Danish drama series - Heram, Yamila (2020)
In Argentina, Danish television drama series such as Borgen, The Killing and The Bridge attract a small and dedicated niche audience that is actively on the look out for new content. A 2017 study of 83 Argentinian viewers found that these “intelligent” series featured interesting characters who were well-acted and were about topics that they could relate to. Authenticity was also important, but this was interestingly undercut by Scandinavian society being, for example, too politically correct and lacking in corruption for an Argentinian audience to consider ‘real’ per se.